MODEL VIDEO PENDIDIKAN GIZI GUNA MENINGKATKAN PEMAHAMAN TERKAIT KONSUMSI PRODUK ULTRA-PROCESSED FOOD PADA REMAJA - Rusfianti, Alfia; Widyaningsih, Vitri; Hikmayani, Nur Hafidha (Poltekkes Kemenkes Bandung, 2024)
The high consumption of ultra-processed food (UPF) among adolescents can increase the prevalence of obesity and non-communicable diseases. Educating adolescents through videos related to UPF consumption may increase knowledge and potentially change their behaviors to choose healthier foods.This study aimed educating adolescents through videos related to UPF consumption may potentially increase their knowledge regarding nutrition and change their behavior to choose healthier foods. We used Research and Development (R&D) approach by adopting the analysis, design, development, implementation, and evaluation (ADDIE) model. The study subjects were a content expert, a linguist, a media expert, and a small group of adolescents. Data were collected using questionnaires and descriptively analyzed. Assessment results from the three experts were 77.1%, 80.0%, and 70.0%, respectively, with an averaged score of 75.1%, suggesting that the educational videos developed were valid, requiring only minor revisions. The revised videos were then validated on a small group of adolescents, with averaged score of 83.90% rendering the videos highly valid to be used as a nutrition education media. Based on these results, it can be concluded that the developed videos about UPF are suitable for use as a nutrition educational media for adolescents.